Effort-Reward Imbalance: A Risk Factor for Exposure to Workplace Bullying - Notelaers, Guy; Törnroos, Maria; Salin, Denise (Frontiers in Psychology, 2019)
Previous research shows that work environment factors are important antecedents of workplace bullying (WB), because of the stress they may induce. While previous studies have typically used Karasek’s Job Demand-Control model or the Demands-Resources model, the present study investigates whether another important occupational stress model, that is the Effort-Reward Imbalance model, is also associated to WB. A survey study in 19 Belgian organizations (n = 5727) confirmed that employees experiencing an imbalance between efforts and reward were more likely to be targets of exposure to bullying. In line with previous research, this study illustrates that stressful situations increase the risk of exposure to WB. It shows that the perceived incongruence between effort and reward may increase employee vulnerability to bullying. The perceived injustice may lead employees to engage in norm-breaking behavior and also signal low social standing to others, thereby potentially eliciting negative behaviors from others.